Cervical spine control; bending the rules. Issue 6 (1st November 2002) - Maskery, N S S; Burrows, N
Abstract : Cervical spine fractures associated with diffuse idiopathic hyperostosis (DISH) are less common than those associated with ankylosing spondylitis and can occur after minor trauma in patients asymptomatic of the disease process. This case report describes a hyperextension injury of the neck in a patient unknown to have DISH, which resulted in an angulated C3/C4 fracture. The position of the fracture was improved by placing the neck in flexion with immediate improvement in the patient's neurological deficit.